The Fourth Arena. Rethinking Political Participation in the Digital Age - Bordignon, Fabio (PARTECIPAZIONE E CONFLITTO, 2025)
The digital revolution and the rise of e-participation have led scholars to reconsider established definitions of political participation: their dimensions, modes, and arenas. Drawing on the theoretical framework proposed by Francesco Raniolo in his book ’La partecipazione politica. Fare, pensare, essere’, this article examines the academic debate surrounding the various definitions of online participation and its intersections with long-standing disputes over the nature of political participation. Treating the media (and the Internet) as an arena for observing citizens’ engagement and participatory acts enables to address the hybrid and expanding repertoire of what will be called Participation at Distance (PaD), which also sees the re-invention of traditional forms of participation. More than other arenas, the media arena constitutes a ’place’ capable of hosting old and new, conventional and unconventional, institutional and non-institutional, instrumental and expressive, legal, a-legal, and illegal forms of political participation.